Proceedings of the 14th Meeting on the Mathematics of Language (MoL 2015) 2015
DOI: 10.3115/v1/w15-2310
|View full text |Cite
|
Sign up to set email alerts
|

Output Strictly Local Functions

Abstract: This paper characterizes a subclass of subsequential string-to-string functions called Output Strictly Local (OSL) and presents a learning algorithm which provably learns any OSL function in polynomial time and data. This algorithm is more efficient than other existing ones capable of learning this class. The OSL class is motivated by the study of the nature of string-to-string transformations, a cornerstone of modern phonological grammars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 26 publications
0
50
0
Order By: Relevance
“…Chandlee defined three subclasses of subsequential functions-Input Strictly Local (ISL) and Output Strictly Local (OSL, Left-OSL and Right-OSL)-and showed that ISL and OSL functions are sufficient to model a range of local phonological processes such as final voice devoicing, insertion, deletion etc. (Chandlee 2014;Chandlee et al 2014;2015). ISL and OSL functions crosscut the subsequential region, as shown in Figure 1, which suggests that local phonological processes are even less complex than subsequential.…”
Section: Ldca Mappings Are Subsequentialmentioning
confidence: 95%
“…Chandlee defined three subclasses of subsequential functions-Input Strictly Local (ISL) and Output Strictly Local (OSL, Left-OSL and Right-OSL)-and showed that ISL and OSL functions are sufficient to model a range of local phonological processes such as final voice devoicing, insertion, deletion etc. (Chandlee 2014;Chandlee et al 2014;2015). ISL and OSL functions crosscut the subsequential region, as shown in Figure 1, which suggests that local phonological processes are even less complex than subsequential.…”
Section: Ldca Mappings Are Subsequentialmentioning
confidence: 95%
“…Admittedly, there is not yet a deep understanding of the formal and learnability properties of subregular functions that can model string-to-string mappings. However, recent work has defined a number of relevant classes and identified some of their formal properties (e.g., Chandlee, 2014;Chandlee, Eyraud, & Heinz, 2015;Mohri, 1997), including a number of promising results regarding learnability (Chandlee, Eyraud, & Heinz, 2014;Chandlee & Jardine, 2014). Of particular relevance is the finding that subsequential functions (Mohri, 1997) characterize many attested patterns of longdistance consonant dissimilation (Payne, 2014) and consonant harmony (Luo, 2017), while excluding a number of complex pathologies.…”
Section: Further Issuesmentioning
confidence: 99%
“…This would open doors to not only better understanding the computational properties of reduplication, but to likewise develop learning algorithms for reduplication. As of now, we hypothesize that a large majority of reduplicative fall under a sub-class of 2-way FSTs (that we have discovered) based on a 2-way extension of the Output-Strictly Local subclass of 1-way FSTs (Chandlee et al, 2015). For more discussion of this subclass for reduplication and its learnability, see Dolatian and Heinz (2018).…”
Section: Resultsmentioning
confidence: 79%
“…Fourth, in the same way that Chandlee 2014; 2017 and Chandlee et al ( , 2015 have studied subclasses of 1-way FSTs and shown how they map to subclasses of morpho-phonology, we are currently investigating what proper subclasses of 2-way FSTs can be designed in order to make a tighter fit with reduplicative typology. This would open doors to not only better understanding the computational properties of reduplication, but to likewise develop learning algorithms for reduplication.…”
Section: Resultsmentioning
confidence: 95%